Outcomes and Complications of Aggressive Resection Strategy for Pituitary Adenomas in Knosp Grade 4 With Transsphenoidal Endoscopy - Ouyang, Taohui; Zhang, Na; Xie, Shenhao; Tang, Bin; Li, Junjun; Xiao, Limin; Zhang, Fabao; Wu, Bowen; Zhou, Dongwei; Li, Meihua; Hong, Tao (Frontiers in Oncology, 2021)
Abstract Surgery for pituitary adenomas (PAs) with cavernous sinus (CS) invasion in Knosp grade 4 is a great challenge and whether to adopt a conservative or aggressive surgical strategy is controversial. The aim of this study is to provide the outcomes and complications of an aggressive resection strategy for Knosp grade 4 PAs with transsphenoidal endoscopic surgery. Outcomes and complications were retrospectively analyzed in 102 patients with Knosp grade 4 PAs. Among them, primary PAs were seen in 60 patients and recurrent PAs were seen in 42 cases. Gross total resection (GTR) of the entire tumor was achieved in 72 cases (70.6%), subtotal tumor resection (STR) in 18 cases (17.6%), and partial tumor resection (PTR) in 12 cases (11.8%). Additionally, GTR of the tumor within the CS was achieved in 82 patients (80.4%), STR in 17 patients (16.7%), and PTR in 3 patients (2.9%). Statistical analyses showed that both recurrent tumors and firm consistency tumors were adverse factors for complete resection (P<0.05). Patients with GTR of the entire tumor were more likely to have favorable endocrine and visual outcomes than those with incomplete resection (P<0.05). Overall, the most common surgical complication was new cranial nerve palsy (n=7, 6.8%). The incidence of internal carotid artery (ICA) injury and postoperative cerebrospinal fluid (CSF) leakage was 2.0% (n=2) and 5.9% (n=6), respectively. Six patients (5.9%) experienced tumor recurrence postoperatively. For experienced neuroendoscopists, an aggressive tumor resection strategy via transsphenoidal endoscopic surgery may be an effective and safe option for Knosp grade 4 PAs.